Detecting Sensor Coordination in a Calibrated Lightning Locating System - Kamyar, Mehranzamir; Hadi Nabipour, Afrouzi; Zulkurnain, Abdul-Malek; Marwan, Nafea; Shirley, Rufus (2019)
A number of applications use the information from lightning locating systems. Public individuals rarely have their own lightning detection networks; thus they rely on national Lightning Locating Systems (LLSs) or weather forecasters. Therefore, local LLS is useful for public to warn them as soon as the sensors detect the lightning strike. An accurate location estimation of Cloud to Ground (CG) flashes is required to be obtained by applying available detecting methods. Common lightning locating system (LLS) uses various detection techniques such as Time Difference of Arrival (TDOA), Magnetic Direction Finding (MDF) and interferometry. However, these techniques have their own positive points and disadvantages. Low accuracy, high cost, time synchronization problems are several of these weaknesses. Therefore, calibrating the lightning detecting sensors has direct impact on the accuracy of a LLS. In this study, a calibrated LLS including the cross loop antennas, parallel plate antennas and GPS cards with data loggers have been installed at each of the three stations to capture the waveforms and to save the time stamps of incoming signals for further analyses. The captured waveforms of a real lightning discharge were investigated to measure the accuracy of a calibrated system.